The Results of Intestinal Villi of Laying Hens Exposed With Avian Pathogenic Escherichia coli (APEC) After Giving Citric Acid and Dextrose - Sunaryo Hadi Warsito; Mirni Lamid; M. Anam Al-Arif; Herry Agoes Hermadi; Emy Koestanti Sabdoningrum; Siti Rani Ayuti; Yan-Der Hsuuw (Veterinary Medicine International)
The condition known as colibacillosis is still very common in Indonesia, which means that laying hens affected by it are unable to achieve their peak egg production phase. Instead, their egg production is delayed and more susceptible to infection by other diseases. The goal of this study is to determine if the mixture of citric acid and dextrose can inhibit the growth of Avian Pathogenic Escherichia coli (APEC) bacteria in laying hens, ultimately leading to the control of colibacillosis cases in Indonesia. A total of 240 laying hen heads in all were split up into 6 treatments, each with 40 replications.The group received the following treatments: T0 is a treatment for laying hens free of APEC infection and they are given no drink that contains any mixture of citric acid and dextrose. T0 (−) is a treatment for laying hens free of APEC infection but a drink mixture of citric acid and dextrose is administered at a dose of 1 g/2.5 L of drinking water. T0 (+) is a treatment for laying hens infected with APEC up to 2 mL/head orally (3 × 108 CFU/mL) and given a drink without the mixture of citric acid and dextrose. T1 is a treatment for laying hens infected with APEC up 2 mL/head orally (3 × 108 CFU/mL) and given a mixture of citric acid and dextrose at a dose of 1 g/1.25 L of drinking water. T2 is a treatment for laying hens infected with APEC up to 2 mL/head orally (3 × 108 CFU/mL) and given a mixture of citric acid and dextrose at a dose of 1 g/2.5 L of drinking water. T3 is a treatment for laying hens infected with APEC up to 2 mL/head orally (3 × 108 CFU/mL) and given a mixture of citric acid and dextrose at a dose of 1 g/3.75 L of drinking water. The results of this study stated that the mixture of citric acid and dextrose showed a significant decrease in the appearance of the intestinal villi of laying hens, because the results were actually less good compared to the treatment infected with APEC. It is suspected that the dose given may still be excessive in concentration. This can be seen from the dose with the highest concentration range (T1) to the lowest (T3) which showed an image of intestinal villi that had a tendency to improve. Therefore, further research and studies are needed regarding the use of a mixture of citric acid and dextrose in laying hens infected with APEC with a lower dose.